Comparison of Disability Indices by Multidimensional Health Assessment Questionnaire and Short Form 36 in Patients of Rheumatoid Arthritis With or Without Fibromyalgia (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Rheumatoid Arthritis (RA) is a chronic disabling and deforming autoimmune disease which presents frequently with articular and extra articular features.Fibromyalgia (FM) has been reported in significant number with RA cases. FM has negative impact on health status, functional capacity, and quality of life. Aim of this study is to assess disability indices Multi-Dimensional Health Assessment Questionnaire (MD HAQ) and Short Form 36 (SF-36) in patient of RA with FM in comparison to RA without FM.Materials and methods: Total 50 patients of RA were enrolled from the Medicine and Physical Medicine Department of Chittagong Medical College Hospital. After clinical evaluation, MDHAQ and SF-36 questionnaires were applied to every patient. Erythrocyte Sedimentation Rate (ESR) and C-reactive Protein (CRP) Rheumatoid Factor (RF) were measured to assess disease activity of RA. FM and RA were diagnosed by American College of Rheumatology Joint count criteria.Results: Meanage was 51.20 (±8.44) years with male to female ratio 1:1.6.Out of 50 RA patients, 11(22%) were classified having FM predominantly in female.Mean (±SD) Disease Activity Score 28 (DAS 28) were significantly higher in patients with RA and FM (5.74±1.09) than in patients with RA only (4.51±1.41). Median MDHAQ scores were significantly higher in patients with RA and FM than the RA patients without FM. SF-36 scores for quality of life in all aspects is significantly worse in RA patients with FM compared to RAwithout FM.Conclusions: RA with FMPatients are found to have worse scores on the MDHAQ and SF-36 than RA alone.JCMCTA 2019 ; 31 (1) : 4-8